Development assistance efforts and policies of the members of the Development Assistance Committee: 1965 review - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1965)
This report follows the completion of the Development Assistance Committee's Annual Aid Review. It is the report of the Chairman, prepared with the advice of the members of the Committee. It is based in large part on the written and oral information given on the various subjects prepared by the O.E.C.D.
usc 07/08/18
Loans
Keywords: Economic assistance; Technical assistance; Economic development; Developing countries